Translanguaging and teacher authority - Brubacher, Katie; Harper, Sarah (Language and Literacy / Langue et littératie, 2024)
The purpose of the paper is to understand the connection between teacher authority and children’s language use. The data presented here was pulled from two large data sources: a set of case-studies in Grades 4 to 6 classrooms with multilingual children who were new to Canada and learning to read and write for the first time and qualitative research in a teacher education program preparing teacher candidates to educate multilingual students. Findings suggest that children translanguage in liminal spaces outside of the teachers’ authority and that multilingual students that were asked to translanguage in English authority classrooms had negative experiences.